Biosafety at the crossroads: An analysis of South Africa's marketing and trade policies for genetically modified products - Gruère, Guillaume P.; Sengupta, Debdatta (International Food Policy Research Institute, 2008)
South Africa is the only country in Africa that has both adopted genetically modified (GM) crops and developed a functional biosafety system to manage any risks related to the use of GM products. But it is also one of the only countries that trade both GM and non-GM crops, despite being surrounded by countries banning the use of GM products. In this paper, we analyze the marketing and trade policies for GM products in South Africa that have been successful in the past and critically review recent reforms to these policies. By providing trade volume estimates of potentially GM products, we show that South Africa is effectively a significant exporter and importer of both GM and non-GM products. We then show that although its import approval system has been effective, recent reforms have allowed regulators to use biosafety regulations as an apparent nontariff barrier to trade. On the export side, South Africa has been able to adapt to each specific demand, but potential export risks have gradually entered the decisionmaking process through the inclusion of socioeconomic considerations. On the marketing side, we show that although non-GM maize segregation has been successful so far, it has generated some adjustment costs and could be improved. At the same time, by excluding all current GM products, the GM food labeling regulation in place has not been fully satisfactory and is bound to change; it could be heading toward a strict mandatory system, despite limited public demand. Therefore, there is a clear movement toward more costly and rigid trade and marketing regulations for GM products in South Africa, with local special-interest groups having an increasing influence on decisionmaking. Yet, the past 10 years have demonstrated that South Africa's success in taking advantage of biotechnologies under changing global conditions stems mainly from its adaptation capacity and the flexibility of its system. Based on the analysis presented in this paper, we provide six policy recommendations to improve rather than rigidify market and trade regulations' policies that would allow South Africa to better adapt to global changes, to manage risks rigorously but efficiently, and to take advantage of safe and potentially promising new GM technologies.